Challenge of complex change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A workshop on 'Agricultural services provision and the challenge of complex organisational change' was held in early December 2000 in Tune, Denmark, with support from Danida and CTA. The several dozen participants, including nine from Kenya,...